Synthesis, characterization, and theoretical studies on N′-furan-2ylmethylene-N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-chloro-acetic acid hydrazide. (12th April 2016) - Demir, S.; Dincer, M.; Cukurovali, A.; Yilmaz, I.
ABSTRACT: The title compound, N ′-furan-2ylmethylene- N -[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-Chloro-acetic acid hydrazide (abbreviated as NNCA), has been synthesized and characterized by elemental analysis, IR, 1 H and 13 C NMR, UV and X-ray single-crystal diffraction. Density function theory (DFT) calculations at the B3LYP/6–31G(d) and 6–31G(d, p) levels for optimized geometries and electronic transition spectra have been performed. İn consequence of computing committed for the title compound, the vibrational analysis, molecular electrostatic potential (MEP), frontier molecular orbitals (FMO), theoretical conformational analyses combining molecular mechanics and thermodynamic properties at different temperatures have been obtained.